Promoting Learning Under the Background of Poverty Alleviation Strategy The Path of Pre-Education Development - Liqun Wu (International Journal of Management and Education in Human Development, 2022)
Children are the future of the country and the hope of the nation, and an important resource for the sustainable development of society. Under the background of poverty alleviation strategy, preschool education has made some achievements, but there are still problems and challenges. In order to consolidate the achievements of expanding education to overcome poverty, it is of great significance to continue to provide quality preschool education for children in poverty-stricken areas, which will lay the foundation for lifelong learning of children in poverty-stricken areas, promote the fairness of social starting point and block the intergenerational transmission of poverty.